PENGARUH LATIHAN SINGLE LEG HOP TERHADAP POWER OTOT TUNGKAI PADA ATLET RANDORI CABOR KEMPO DOJO BANGKINANG - Muhammad Thoib; Slamet Slamet; Arif Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to determine whether there is influence of Single Leg Hop exercise on leg muscle power at Athletes Randori cabor Kempo dojo Bangkinang so that when doing kicks get the desired power. The design of this study used the observation method with one-group technique pretest-postest with sampling according to the acquisition of total sampling technique amounted to 7 people. Instrument used in this research is Vertical Power Jump Test which aims to measure limb muscle power athletes randori cempo kempo where data collected through preliminary test and final test Vertical Power Jump Test. The test result data is then processed using statistics to test the normality by lilifost test at a significant level α = (0.05). Based on the analysis of statistical data obtained pre-test data Lcount of 0.1769, post-test data Lcount of 0.1844 and Ltable 0.300. Further analysis of t test obtained by Tcount of 14.21 and Ttable 1.943. Thus it can be concluded that there is the influence of single leg hop training on leg muscle power in Athletes Randori cabor Kempo dojo bangkinang.Key Words: Single Leg Hop, Limb Muscle Power.